The color of Christ: the Son of God & the saga of race in America - Blum, Edward J. (Univ. of North Carolina Press, 2012)
When Christ crossed the Atlantic -- Revolutionary visions in colonial confines -- From light to white in the early republic -- Body battles in antebellum America -- Christ in the camps -- Nordic and nativist in an age of imperialism -- The great commission in the Great Depression -- Civil rights and the coloring of Christ -- A deity in the digital age -- Epilogue: Jesus jokes